The Effect of Training on Employee Performance: A Case Study of Employees in the Food and Beverage Service Department at The Laguna, a Luxury Collection Resort and Spa - Dewi, Ni Made Ratih Kumala; Sihombing, Irene Hanna H.; Witarsana, I Gusti Agung Gede (Program Studi Administrasi Perhotelan, 2023)
This study was conducted to determine the effect of training on food and beverage service employees’ performance at The Laguna, a Luxury Collection Resort and Spa. Data collection techniques used in this study were interviews, questionnaires, and literature reviews. 52 respondents from all employees of the food and beverage service department at The Laguna, a Luxury Collection Resort and Spa were involved. The sampling technique used was the saturated sampling method, in which all population members were used as samples. The data analysis method used was the validity test, reliability test, simple linear regression, t-test, and determination coefficient test which was assisted by SPSS version 23 for Windows. The results of this study indicate that job training has a positive and significant effect on employee performance. This can be proven by a significance value of 0.000 < 0.05 with a value of tcount > ttable = 15.636 > 2.008. Based on the analysis of the determination coefficient, job training has a strong influence of 83% on employee performance, while other factors outside of this study influence the remaining 17%. This research is expected to be used as consideration for The Laguna, a Luxury Collection Resort and Spa to determine policies that aim to improve the performance of food and beverage service department employees through job training programs.